The UL45 gene product is required for herpes simplex virus type 1 glycoprotein B-induced fusion. - Haanes, E J (1994)
Herpes simplex virus type 1 (HSV-1) syncytial (syn) mutants cause formation of giant polykaryocytes and have been utilized to identify genes promoting or suppressing cell fusion. We previously described an HSV-1 recombinant, F1 (J.L. Goodman, M. L. Cook, F. Sederati, K. Izumi, and J. G. Stevens, J. Virol. 63:1153-1161, 1989), which has unique virulence properties and a syn mutation in the carboxy terminus of glycoprotein B (gB). We attempted to replace this single-base-pair syn mutation through cotransfection with a 379-bp PCR-generated fragment of wild-type gB. The nonsyncytial viruses isolated were shown by DNA sequencing not to have acquired the expected wild-type gB sequence. Instead, they had lost their cell-cell fusion properties because of alterations mapping to the UL45 gene. The mutant UL45 gene is one nonsyncytial derivative of F1, A4B, was found to have a deletion of a C at UL45 nucleotide 230, resulting in a predicted frame shift and termination at 92 rather than 172 amino acids. Northern (RNA) analysis showed that the mutant UL45 gene was normally transcribed. However, Western immunoblotting showed no detectable UL45 gene product from A4B or from another similarly isolated nonsyncytial F1 derivative, A61B, while another such virus, 1ACSS, expressed reduced amounts of UL45. When A4B was cotransfected with the wild-type UL45 gene, restoration of UL45 expression correlated with restoration of syncytium formation. Conversely, cloned DNA fragments containing the mutant A4B UL45 gene transferred the loss of cell-cell fusion to other gB syn mutants, rendering them UL45 negative and nonsyncytial. We conclude that normal UL45 expression is required to allow cell fusion induced by gB syn mutants and that the nonessential UL45 protein may play an important role as a mediator of fusion events during HSV-1 infection.